Carbon emission of urban vehicles based on carbon emission factor correlation analysis - Jingwen Wang; Hongna Dai; Haixia Feng; Meng Guo; Vladimir Zylianov; Zhongke Feng; Jipeng Cui (Scientific Reports)
Abstract The CO2 emission factor is the basis for analyzing vehicle CO2 emissions. This study establishes a correlation model between the fuel CO2 emission factor and the mileage-based CO2 emission factor using fuel consumption data, then analyzes the fuel consumption and CO2 emission situation of vehicles in Beijing with the established models. The main research conclusions are as follows: The proposed correlation models are effective for analyzing urban vehicle CO2 emissions. Cars can only meet the national standard limit when traveling at an average speed of 42.17 km/h. During rush hours, fuel consumption in most cities in China exceeds national standards, making it urgent to improve urban traffic efficiency. Due to the decline in urban traffic conditions in Beijing in 2023 (average speed decreased from 29.14 km/h to 24.26 km/h), each passenger car consumes an average of 0.282 L more gasoline per day, emitting an additional 619.87 g of CO2. This study is of great significance for energy conservation and emission reduction in road transportation.